Pengembangan Materi Fikih Jenjang SMP Pada Indahnya Berpuasa di Kelas VIII - Zaitun Sulaiman; Faridi Faridi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
The purpose of this study is to understand the extent to which fasting material is taught in class VIII junior high school. This research uses the literature study method, in which data is collected from the fiqh teacher's book and student book in the class. The data obtained were then analysed and presented. The results showed that the material on fasting in the fiqh textbooks of grade VIII students was still lacking in depth and breadth. Therefore, it is expected that teachers can enrich the material taught by considering facts, concepts, principles, and procedures that must be clear, functional, valuable, and easy to understand. This step is taken to ensure that students not only know the development of science and technology but can also balance it with the religious knowledge they learn. It is hoped that the research activities that include the revision and development of fiqh subject matter will yield positive results. The new fiqh materials are expected to be more weighty, effective, and easier to understand by both teachers and students.